Impact ionization dust detection with compact, hollow and fluffy dust analogs. (1st October 2022) - Hunziker, S.; Moragas-Klostermeyer, G.; Hillier, J.K.; Fielding, L.A.; Hornung, K.; Lovett, J.R.; Armes, S.P.; Fontanese, J.; James, D.; Hsu, H.W.; Herrmann, I.; Fechler, N.; et al.
Abstract: Impact ionization of high-velocity cosmic dust particles has been used as a basic principle for dust detectors in space for many decades. It has provided optimum means to gain insight into the dust environment in the solar system. The Ulysses Dust Detector System provided for the first time impact ionization-based detection of interstellar dust (ISD) in the solar system and discovered surprisingly heavy ISD particles with sizes up to a few microns. Studies based on astronomical observations of the local interstellar medium, on the other hand, suggested a much smaller upper limit of around 0.25 ​μm (silica) or 1 ​μm (graphite) for the size distribution of ISD particles. Therefore, it has been suggested that low-density fluffy dust particles may mimic the impact signals of heavier compact particles. In this work, we discuss a series of impact experiments that have been performed at the Heidelberg dust accelerator facility with the Cosmic Dust Analyzer flight spare unit, to compare the high-velocity impact ionization properties of compact and hollow silicate particles, and carbon aerogel particles with each other and with literature data. The experiments indicate differences in the collected total amount of impact charges and how quickly the charges are collected, between impacts from compact particles and their non-compact counterparts. The results of this first study suggest that fluffy particles generate less ions upon impact than their compact counterparts, opposite to the suggested explanation for the heavy ISD particles. Data from the performed impact experiments indicate that a secondary process (e.g. secondary impacts from ejecta or more target material ionization) could be the main cause for the observed differences. These results imply that the previously detected heavy ISD particles may be real. We identify the key problems with the performed dust experiments and advise that future impact ionization instruments should additionally be calibrated with improved low-density fluffy dust particles that better represent the properties of cosmic dust particles. Highlights: Shows new results for impact ionization experiments with non-compact dust particles. Secondary ionization processes may depend on particle structure and density. Impact ejecta and target ionization are candidates for relevant secondary processes. Large and porous in situ interstellar dust particles might likely be real.